Depressão materna no período perinatal e macroarquitetura do sono ao final do primeiro ano de vida - El Halal, Camila dos Santos (2018)
The period extending from pregnancy to the months following delivery, although usually associated to positive feelings, represents a moment of great vulnerability to the development of major depressive disorders. Perinatal depression is a frequent pathology, and its consequences extend beyond the mother, potentially affecting the relationship with her partner and family functioning. Early exposure to maternal depression is associated to lower breastfeeding rates, impairment of mother-infant bonding, and consequences over child growth and development. Perinatal depression has been linked to infant sleep disturbances as early as in the neonatal period, with description of more night wakings, shorter sleep duration and more fragmented sleep. Sleep plays a fundamental role in child cognitive, social, and emotional development, and its disturbances, in a crucial moment of brain development, may facilitate significant and persistent dysfunctions. Studies associating maternal depression to child sleep disturbances show important heterogeneity in terms of design as in moment of sleep assessment. Sleep patterns go through important changes throughout the first twelve months of life, rendering impaired the association’s precise evaluation, as well as that of its potential long-term consequences. This study aimed to investigate the association between perinatal depression and altered infant sleep macrostructure at one year of life among participants in a birth cohort. In this population-based study, recruitment was carried out from pregnancy to soon after delivery, aiming to include all livebirths in the municipality of Pelotas throughout the year of 2015. Participants to one or both cohort-nested trials and those lacking information on maternal depression were excluded from these analyses. For the diagnosis of perinatal depression, the Edinburgh Postnatal Depression Scale (EPDS) was completed during pregnancy and 3 months after delivery, having been considered perinatally depressed mothers who scored ≥13 points in one or both follow-ups. Infant sleep was assessed at 3 months through the Brief Infant Sleep Questionnaire (BISQ) and, at 12 months, through the same subjective questionnaire added to objective data derived from continuous 24-hour actigraphy. Main sleep outcomes were number of night time wakings, night vigil time and total sleep duration in 24 hours. The sample consisted of 2222 mothers/infants, in which prevalence of perinatal depression was of 22.3% (CI 95% 20.5-24). Adjusted analyses using Poisson’s regression from BISQ-derived data showed greater risk of >3 night time wakings at 12 months among infants of depressed mothers (RR 1.52; CI 95% 1.06-2.18; p=0.02). Actigraphic data did not, however, confirm those findings (adjusted RR=1.24; CI 95% 0.85-1.81; p=0.26). No association was found between perinatal depression and the other investigated sleep variables. This study suggests a potential defining role of dysfunctional cognition among mothers with a history of perinatal depression on infant sleep characteristics at the end of the first year of life.